Hermenêutica botânica e antropização na Amazônia: exsicatas de Verbenáceas da Amazônia Legal no Herbário do New York Botanical Garden - Guerra, Gutemberg Diniz; Menesez, Maria de Nazaré Angelo; Ming, Lin Chau [UNESP] (My University, 2011)
This article is based on information from a historical series of dried herbarium specimens dating from 1819 to 2002, bringing together contributions from researchers in both governmental and nongovernmental organizations from North and South America as well as from Europe. The focus is on Verbenaceae by its recognized range of aromatic and medicinal species of this family and its recognized use in Brazil. The study examines descriptive and critical notes from the New York Botanical Garden collection relating to the Amazonia, revealing the spirit of cooperation between Brazilian and foreign institutions in this region. Changes in the environment, network of researchers, changes in the language system, technology records and absorption of regional terms are detected over almost two centuries of scientific work that projects the continued training of scientists with local knowledge and interaction.

Este artigo tem como base informações de uma série histórica de exsicatas datadas de 1819 a 2002, reunindo contribuições de pesquisadores de instituições governamentais e não governamentais das Américas do Norte, do Sul e Europa. Tem foco nas verbenáceas, pela reconhecida gama de espécies aromáticas e medicinais desta família e o seu reconhecido uso no Brasil. Analisa notas descritivas e críticas sobre a coleção do New York Botanical Garden referente à Amazônia, revelando o espírito da cooperação entre instituições brasileiras e estrangeiras nesta região. Alterações do meio ambiente, rede de pesquisadores, mudanças na linguagem, na tecnologia dos registros e absorção de termos regionais são detectados ao longo de quase dois séculos de trabalho científi co em que se projeta a formação continuada de cientistas e a interação com saberes locais.
Botanical hermeneutic and anthropization in the Amazon: Exsicatas of Verbenaceae from the Brazilian Amazon in the New York Botanical Garden Herbarium
Keywords: Scientific interchange; Botanic; Herbarium specimens; Taxonomy; Expedition; Photography; Intercâmbio científico; Botânica; Exsicatas; Taxonomia; Expedições; Fotografia